Observation-based temperature field simulation at Zhurong landing site, Mars - Zhang, Lei; Zhang, Jinhai (Frontiers in Astronomy and Space Sciences, 2022)
Modeling the temperature field near the Martian surface is critical for many scientific exploration tasks, such as detecting liquid water and analyzing the existence of saline ice. Meteorological conditions on Mars are highly dramatic, with a daily temperature change of up to 80–100 K. Most previous tasks of surface temperature monitoring on Mars are based on satellite observations, lacking in-situ measured data. Recently, two Martian missions at mid-low latitudes in the northern hemisphere, InSight lander and Zhurong rover, carried out near-surface temperature observations. However, the temperature monitoring of the Zhurong rover obtained data for only some short periods in its working days; thus, the amount of recorded temperature data is inadequate for a whole-day analysis at the landing site. Here we reconstruct the near-surface temperature at the Zhurong landing site by incorporating the continuous temperature data observed at the InSight lander, simultaneously referring to the Martian Climate Database; then, the reconstructed data are used to constrain the numerical simulation of the response of shallow subsurface under the Zhurong landing site. The numerical simulation of heat conduction shows that the daily temperature change under the Zhurong landing site mainly influences the uppermost depth of 0-30 cm, with a daily average temperature of ~225 K. During the traveling duration of the Zhurong rover (i.e., summer of Mars), the seasonal temperature change within the top 1 m is significant and is related to the thermal properties of possible subsurface media (e.g., soil, ice, and sandstones). Although there might be aqueous activities in Utopia Planitia, our results show that from the perspective of temperature field, there is little possibility of liquid water in the shallow subsurface under the Zhurong landing site. The proposed method in this study provides a new way for the temperature field simulation of the subsurface in areas with insufficient local observations, especially on extraterrestrial objects.